Determination of Irrigation Time Using Plant Water Stress Index Values of Second Crop Sunflower in Semi-Arid Climate Conditions - Ali Beyhan uçak; Halis Seçme (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out in 2020 to determine crop water stress index (CWSI) by using infrared thermometer (IRT) data calculated by leaf canopy temperature measurements of the second crop sunflower genotype in semi-arid climate conditions, and to determine the relationships between irrigation time, seed yield of sunflower plant and CWSI by using these index values. Irrigation program consisted of a full irrigation and 2 different levels of stress, which were 100% (I100), 70% (I70), 35% (I35) of water losses within the effective root depth of 90 cm every 7 days. A total of 644 mm of irrigation water was applied to I100 (control) irrigation. The water consumption for full irrigation was 721 mm and the yield was 3516.00 kg/ha. Lower limit (LL) value without water stress required to determine plant water stress index was Tc-Ta=-2.528×VPD +0.749 (R2=0.814) and upper limit (UL) value, where the plant is completely under water stress, was determined as +3.27℃. Crop water stress index value threshold at which sunflower seed yield started to decrease was calculated as 0.33 using the infrared thermometer measurements at the time of irrigation. In addition, a negative correlation was obtained between sunflower seed yield and CWSI values. The results revealed that the yield tends to decrease as the CWSI increases.